Evaluation of a novel, ultrathin, tip-bending endoscope in a synthetic force-sensing pancreas with comparison to medical guide wires - Chandler JE (Dove Medical Press, 2011)
John E Chandler1, Cameron M Lee1, Alexander P Babchanik1, C David Melville1, Michael D Saunders2, Eric J Seibel11Human Photonics Laboratory, Department of Mechanical Engineering, University of Washington, Seattle, WA, USA; 2Digestive Disease Center, University of Washington Medical Center, Seattle, WA, USAPurpose: Direct visualization of pancreatic ductal tissue is critical for early diagnosis of pancreatic diseases and for guiding therapeutic interventions. A novel, ultrathin (5 Fr) scanning fiber endoscope (SFE) with tip-bending capability has been developed specifically to achieve high resolution imaging as a pancreatoscope during endoscopic retrograde cholangiopancreatography (ERCP). This device has potential to dramatically improve both diagnostic and therapeutic capabilities during ERCP by providing direct video feedback and tool guidance to clinicians.Methods: Invasiveness of the new tip-bending SFE was evaluated by a performance comparison to ERCP guide wires, which are routinely inserted into the pancreatic duct during ERCP. An in vitro test model with four force sensors embedded in a synthetic pancreas was designed to detect and compare the insertion forces for 0.89 mm and 0.53 mm diameter guide wires as well as the 1.7 mm diameter SFE. Insertions were performed through the working channel of a therapeutic duodenoscope for the two types of guide wires and using a statistically similar direct insertion method for comparison to the SFE.Results: Analysis of the forces detected by the sensors showed the smaller diameter 0.53 mm wire produced significantly less average and maximum forces during insertion than the larger diameter 0.89 mm wire. With the use of tip-bending and optical visualization, the 1.7 mm diameter SFE produced significantly less average force during insertion than the 0.89 mm wire at every sensor, despite its larger size. It was further shown that the use of tip-bending with the SFE significantly reduced the forces at all sensors, compared to insertions when tip-bending was not used.Conclusion: Combining high quality video imaging with two-axis tip-bending allows a larger diameter guide wire-style device to be inserted into the pancreatic duct during ERCP with improved capacity to perform diagnostics and therapy.Keywords: endoscopic retrograde cholangiopancreatography (ERCP), scanning fiber endoscope (SFE), pancreatic cancer, minimally invasive therapy